UTILIZING SCRABBLE AS A MEDIUM TO IMPROVE STUDENTS’ VOCABULARY SKILLS IN HIGH SCHOOLS - Irfan Hadi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
A good education produces satisfactory learning outcomes. Creative learning requires teachers to be able to use all available resources so that students learn optimally. One of the efforts to maximize learning at home is the use of appropriate media for the conditions and situations at school. The teachers’ difficulty of using suitable media is a problem, especially the teaching of English words. Students still have insufficient vocabulary mastery; as a result,innovations and effort are required in order that students can improve their learning outcomes. One of the media that can be used is scrabble. This research used classroom action research method. The class action was carried out in 2 cycles. The initial cycle began with mapping the students' initial abilities and administering a test after using Scrabble. The second cycle was conducted by improving the teaching through scrabble. 21 students were involved in the classroom action research. The results showed that scrabble could improve English vocabulary learning outcomes. The average score in cycle 1 was 77.9 and in cycle 2 was 78.9. There was an increase for1 point. This result was expected to be improved as the students' vocabulary increased. Teachers should be able to use various and effective media so that students would not get bored studying in class. Learning outcomes increased along with the increase in students’ activities in the classroom.